Global perspectives on industrial transformation in the American South - Delfino, Susanna, 1949-; Gillespie, Michele (New currents in the history of Southern economy and society., 2005)
"Essays analyzing the economic evolution of the American South from the late colonial period to World War I and beyond. Examines the South in respect to long-held assumptions about industrialization and productivity and draws comparisons to the larger Atlantic and world economy"--Provided by publisher.